Hooked: How Politics Captures People's Interest By Markus Prior (ETNOSIA : Jurnal Etnografi Indonesia, 2021)
This article aims to review a book entitled Hooked: How Politics Captures People's Interest (2018). This book is a work that tries to show how this interest in politics arises under several conditions. This book shows how several aspects are important factors in shaping one's interest in politics. Based on research data conducted from four countries that are claimed to be democratic countries, namely the United States, United Kingdom, Germany, and Switzerland, this book shows data on the conception of political interest by examining the influence of aspects of education, profession, and the position of parents. as well as ownership of certain income. This book succeeds in offering a fairly comprehensive analysis in understanding how human interest in politics can be formed.
Keywords: Interest; Politic; Democracy; Influence.